The relationship between conflict with doctors and lack of experience with Death and dying and the level of occupational stress experienced by nurses at Haji Hospital UIN Syarif Hidayatullah Jakarta - Agustianti, Erika; Srisantyorini, Triana; Fauziyah, Munaya; Purnamawati, Dewi; Djauharoh, Siti Nur Aisyah (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2024)
Background and Purpose: This study investigates the relationship between conflict with doctors, lack of experience with Death and dying, and the level of occupational stress among nurses at Haji Hospital UIN Syarif Hidayatullah Jakarta. The aim is to identify contributing factors to workplace stress and inform interventions to improve nurses' well-being and the quality of healthcare services.Methods: A cross-sectional analytical study was conducted involving all 96 nurses at Haji Hospital UIN Syarif Hidayatullah Jakarta. Data was collected using Expanded Nursing Stress Scale (ENSS) to asses hazard psychosocial and Workplace Stress Scale (WSS) to evaluate occupational stress levels through a Google Form. The study examined the association between conflict with doctors and lack of experience with Death and dying (independent variables) and the nurses' reported stress levels (dependent variable).Results: The study revealed a significant association between conflict with doctors and occupational stress (p=0.000), with nurses experiencing conflict being 6.13 times more likely to experience occupational stress (95% CI: 2.337-16.106). A significant relationship was also found between limited experience with Death and dying and occupational stress (p=0.017), with nurses having limited experience facing a 2.07-fold increased risk of occupational stress (95% CI: 1.188-3.612).Conclusion: The occupational stress experienced by nurses at Haji Hospital UIN Syarif Hidayatullah Jakarta is significantly related to conflict with doctors and limited experience in managing Death and dying situations.